Buoyancy effect on the mixed convection flow and heat transfer of supercritical R134a in heated horizontal tubes. (December 2019) - Tian, Ran; Wei, Mingshan; Dai, Xiaoye; Song, Panpan; Shi, Lin
Graphical abstract: Highlights: Buoyancy effect mechanism in horizontal supercritical flow is studied numerically. k top < k bottom is the dominating factor resulting in T w, top > T w, bottom . k top > k bottom owing to newly developed vortexes near the top in strong-buoyancy cases. Effects of diameter and pressure on heat transfer are analyzed. Abstract: Thermal non-uniformity in the horizontal mixed convection heat transfer of fluids at the supercritical pressure is a major issue that must be addressed in a trans-critical organic Rankine cycle. However, the heat transfer mechanism is not fully understood. To further investigate the mechanisms of the buoyancy effect and property variations in a horizontal supercritical flow, mixed convection with supercritical pressure R134a is studied numerically herein using the AKN turbulence model. When the buoyancy effect is weak, the difference in the turbulent kinetic energy with k top < k bottom is the dominating factor resulting in a non-uniform heat transfer. In a strongly buoyancy-affected mixed convection, the flow process is divided into three regions. In region I ( T w increasing section) and region III (gas-like section), k top < k bottom because of the greater velocity gradient at the bottom; in region II, where T w, top reaches a peak and subsequently decreases, k top > k bottom is observed because the newly developed vortexes near the tube top intensifies the turbulence near the top. Heat transfer cases with various tube diameters and pressures are discussed. A stronger buoyancy effect is developed in larger tubes. No new vortex is formed in a 2-mm tube while multiple vortexes are developed in the upper region of 16-mm and 26-mm tubes, providing stronger turbulence for the heat transfer recovery. As the specific heat is sensitive to the pressure variation while the density variation with pressure is moderate, the pressure has less effect on heat transfer in a strong-buoyancy case than in a weak-buoyancy case.